The taxonomic status of the Castelo dos Sonhos Hantavirus reservoir, Oligoryzomys utiaritensis Allen 1916 (Rodentia: Cricetidae: Sigmodontinae) - Agrellos, Rodrigo; Bonvicino, Cibele R.; Rosa, Elizabeth Salbé T.; Marques, Aparecido A.r.; D’andrea, Paulo S.; Weksler, Marcelo (Zootaxa, 2012)
Species of the genus Oligoryzomys are commonly found accross Latin America, and several of them play important rolesas natural reservoirs of Hantaviruses. Here we demonstrate that O. utiaritensis, the natural reservoir of hantavirus Castelodos Sonhos in northwestwern Brazil and previously considered a junior synonym of O. nigripes or O. eliurus, is a validspecies. Morphology, morphometry, karyotyping, and phylogenetic reconstructions based on nuclear (intron 7 of the beta-fibrinogen gene) and mitochondrial (cytochrome b) DNA show that O. utiaritensis differs from O. nigripes and from otherforms of the genus, including the recently described taxon O. moojeni. Oligoryzomys utiaritensis differs in external (whit-ish ventral pelage and tail weakly bicolored) and cranial (incisive foramina never extending posteriorly the alveolus lineof M1) characters from sympatric species. It has the highest diploid number (2n=72) within Oligoryzomys, and is charac-terized by three putative synapomorphies in cytochrome b, and one in intron 7 of beta fibrinogen. We also point to theassignment of Oligoryzomys eliurus as a junior synonym of O. nigripes. Finally, we present phylogenetic analyses of in-trageneric relationships showing that O. utiaritensis is a member of a clade containing Amazonian and Cerrado taxa, including O. moojeni, O. rupestris, and O. delicatus.